PERBANDINGAN EFEKTIFITAS DAN EKONOMIS PEKERJAAN OVERHAUL MESIN DARI 3 INDUSTRI MARITIM DENGAN SKALA BESAR, MENEGAH, DAN KECIL - wafa dwi ari salman (Applied Science and Technology on Naval Engineering, 2024)
In operation, ships have various components. Machinery is a component that has an important role so that ships can move and operate. Therefore, maintaining the performance and condition of ship engines is a must, so that it does not have an impact on ship operations. For this reason, ship owners must carry out routine maintenance and repairs, known as overhauls. In carrying out overhaul activities. On this basis, there are various companies in the maritime industry sector that focus on maintenance or overhaul of ship engines, both in large, medium and small scale maritime industries. The effectiveness of the overhaul process will be assessed using the OEE (Overall Equipment Effectiveness) method and for Looking for economics, the markup pricing method is used and they will be compared with each other to find out who is the most economical. Keywords: Ship, Machinery, Overhaul, Effectiveness, Economical